E-commerce Business Directions of OTOP - Sukrat, Supattana (University of the Thai Chamber of Commerce Journal Humanities and Social Sciences, 2018)
The study aims to investigate the business directions of e-commerce for OTOP. The sample of this study was from 31 out of the population of 125 entrepreneurs of e-commerce establisments in the category of handicraft and OTOP projects registered with the Department of Business Development, Ministry of Commerce. Online questionnaires were collected via email and telephone contact; and data were analyzed in terms of percentage, arithmetic mean and standard deviation via SPSS softwarw. The results showed that most of the respondents were female with Bachelor's degree. Most of them had 2-5 years of experience in website administration and had been in operation for 2-3 years. After operating e-commerce, the percentages of profit increased less than 5 percent. Developing e-commerce website by website service provider. Most of the products sold were handicraft and souvenirs. The results revealed that for business directions, a faw factors are highly important, namely, trust, frequency of email correspondence with customers, quick delivery, interesting website name, and means of customer contact. On the other hand, the three guideline items rated at low level were offline marketing, affiliate marketing and rich media marketing